Desain bifunctional shelter : sebuah desain prototipe bangunan dwifungsi era pandemi - Previari Umi Pramesti (Jurnal Proyek Teknik Sipil, 2022)
Natural disasters and unprecedented explosions provide experience in preparing for, responding to and mitigating their impact on society. Well-managed refugee quarantine and hospitalization in crisis areas greatly reduces the impact on the community and the region itself. However, management and impact reduction must not stop after a disaster or explosion occurs, but sometimes requires a continuous recovery system program, especially in the economic field. The purpose of this research is to create a model of a quarantine house for evacuees after a disaster or epidemic response. The challenge of this model is to create affordable housing that is quick to build, easy to move, uses durable materials and is livable. In addition, this shelter design can be reused for economic activities such as selling capsules to respond to sustainability programs, especially in the economic field. It is hoped that this research can contribute to designing results that can be easily implemented and replicated for improving welfare during and after a disaster or pandemic.